2019
DOI: 10.21037/jtd.2019.02.34
|View full text |Cite
|
Sign up to set email alerts
|

Psychological support of esophageal cancer patient?

Abstract: Important questions are still open about psychological aspects in esophageal cancer (EC) and about the related psychological support. How to cope with the cancer diagnosis and poor prognosis: a psychological counselling may be a valid option to personalize the communication to patients with a poor prognosis. How to cope with long chemoradiotherapy: after neoadjuvant therapy, patients know that curative process is not completed, and they perceive the severity of the neoadjuvant side effects, considering themsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…Another reason might be that there was insufficient emphasis on the importance of mental health at the beginning of the program. Mental health is an important problem in patients with esophageal cancer, as many of these patients experience depressive symptoms and anxiety after surgery [ 53 , 55 ]. Future interventions should emphasize the importance of mental health issues and educate patients to pay attention to their mental wellness after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason might be that there was insufficient emphasis on the importance of mental health at the beginning of the program. Mental health is an important problem in patients with esophageal cancer, as many of these patients experience depressive symptoms and anxiety after surgery [ 53 , 55 ]. Future interventions should emphasize the importance of mental health issues and educate patients to pay attention to their mental wellness after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…1 Most others undergo combinations of radiotherapy, chemotherapy and endoscopy with curative or palliative intent for relieving symptoms. [9][10][11] These patients also have complex needs that require support. [9][10][11] Guidelines on caring for patients with cancer emphasise the need for a holistic approach that addresses patientspecific needs and improving patients' quality of life at all stages of the patient pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Patients may undergo extensive, life-changing surgery with high postoperative morbidity. 9 They often require extensive support for nutritional needs after their surgery but also have complex psychological, emotional, spiritual and social needs. 10 However, surgical resection with curative intent, where surgery is performed to fully remove all cancerous tissue, is only appropriate for 19% of patients at diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal cancer(EC) patients often experience several gastrointestinal (GI) symptoms (1), undergo invasive investigations, suffer from fear of being diagnosed with cancer (2). Furthermore, studies demonstrated multifaceted challenges including reduced physical activity, economic constraints(2, 3), loss of appetite, anxiety, and depression (4).…”
Section: Introductionmentioning
confidence: 99%